Evaluation of effects of dentin bonding agents on microleakage in composite restorations - Pahlevan A.; Rahebi SH (Tehran University of Medical Sciences, 2002)
Dentin bonding agents create stronger bonding between dental composites and dentin. But, none of them can prevent the microleakage. The important factors of progressing microleakage are the stress of polymerization shrinkage of resin composite and removal of smear layer in total-etch technique. The aim of this study was the evaluation of the effect of experimental method (modifying smear layer and etching of enamel margin) and comparison with the total-etch technique. In this experimental method, 60 extracted human molar teeth were disinfected. Then, class 5 cavities were prepared on the buccal surface and 1 mm above CEJ. The specimens were divided randomly to 6 groups with iO samples in each group. The specimens groups were:"n1- Scotchbond Muiti- Purpose Plus Adhesive System (S.B.M.P.P) +Tetric composite"n2- S.B.M.P.P + Ariston composite"n3- Ariston liner + Ariston composite"n4- S.B.M.P.P without enamel and dentin etching + Tetric composite + rebonding with Flowable Tetric"n5- S.B.M.P.P without enamel and dentin etching + Ariston composite + rebonding with Flowable Tetric"n6- S.B.M.P.P without enamel and dentin etching + Tetric composite"nAfter finishing and polishing, the specimens were termocycled, stained with fushin, sectioned within the specimens and evaluated for dye penetration with stereomicroscope. Wilcoxon Sign and Kruskal Wallis tests were used for statistical analysis."nResults showed that group 3 had microleakage more than groups of 1, 2 and 5 (P<0.0 5) and this difference was significant. There was no significant difference among the other groups.